Protective effect of rhizome extracts of the herb, vacha (Acorus calamus) against oxidative damage: An in vivo and in vitro study - M. Devaki; R. Nirupama; M. Nirupama; H.N. Yajurvedi (Food Science and Human Wellness)
The rhizome of Acorus calamus, an herb widely used in Indian system of medicine for many ailments including epilepsy, mental illness and rheumatism, was subjected to soxhlet extraction to elucidate antioxidant property of different solvent extracts using in vitro assays. The benzene extract was most potent in scavenging hydroxyl and superoxide radicals and in reducing 1,1-diphenyl-2-picryl hydrazyl and ferric reducing antioxidant power. In addition the benzene extract prevented oxidative damage to DNA and mitochondria. It was also effective in preventing stress -induced decrease in total plasma anti-oxidant activity as determined in vivo using rat model wherein stress was induced by exposing to restraint and forced swimming. The minimum effective dose of the benzene extract was 5 mg/kg body weight (oral), and at this dose, its effect was similar to the same dose of a standard anti-oxidant, ascorbic acid. The study for the first time, clearly demonstrates a potent anti-oxidant activity of A. calamus combining in vitro and in vivo results. Hence, the therapeutic value of this herb maybe due to its anti-oxidant property.